Advances in BCR/ABL positive ALL. Issue 3 (13th May 2019) - Horowitz, Netanel A.; Rowe, Jacob M.
Abstract: The advent of tyrosine kinase inhibitors (TKIs) has ushered in a new era in the management of patients with Philadelphia chromosome‐positive acute lymphoblastic leukemia (Ph+ ALL). Although, as a group, these inhibitors have led to one of the most successful targeted therapies in leukemia, Ph+ ALL still remains a formidable disease. Unlike chronic myeloid leukemia (CML) where TKIs lead to dramatic long‐lasting responses as single agents, the biology of Ph+ ALL is far more complex and adjunctive therapies are mandatory. These may include corticosteroids, chemotherapy, antibody‐based therapies or, even, allogeneic hematopoietic cell transplantation. Clearly, other genes or mutations are in place that affect the outcome of Ph+ ALL. Additional chromosomal abnormalities are common in Ph+ ALL and have a varying impact on prognosis; some adverse, others less so. Genomic alterations have come into their own in the last decade and have increased our understanding of the mechanisms of resistance and differing responses to therapy. In this review, these genetic aberrations will be considered in some detail. In addition, innovations in current practice – including the use of immunological therapies – will be carefully reviewed. For the first time in decades, the long‐held imperative requiring an allogeneic transplant for a curative approach in adult Ph+ ALL is now being questioned and clinical trials are underway to resolve this issue. However, despite much progress in the past two decades, both in the biology and therapy of Ph+ ALL, this disease still presents a compelling challenge and much remains to be overcome.